Clinical evaluation of a new pupil independent diffractive multifocal intraocular lens with a +2.75 D near addition: a European multicentre study - Kretz, Florian Tobias Alwin; Gerl, Matthias; Gerl, Ralf-Hellmar; Müller, Matthias; Auffarth, Gerd U. (British journal of ophthalmology, 2015)
To evaluate the clinical outcomes after cataract surgery with implantation of a new diffractive multifocal intraocular lens (IOL) with a lower near addition (+2.75 D.).